Reliability Assessment of Transformerless PV Inverters considering Mission Profiles - Yongheng Yang; Huai Wang; Frede Blaabjerg (International Journal of Photoenergy)
Due to the small volume and high efficiency, transformerless inverters have gained much popularity in grid-connected PV applications, where minimizing leakage current injection is mandatory. This can be achieved by either modifying the modulation schemes or adding extra power switching devices, resulting in an uneven distribution of the power losses on the switching devices. Consequently, the device thermal loading is redistributed and thus may alter the entire inverter reliability performance, especially under a long-term operation. In this consideration, this paper assesses the device reliability of three transformerless inverters under a yearly mission profile (i.e., solar irradiance and ambient temperature). The mission profile is translated to device thermal loading, which is used for lifetime prediction. Comparison results reveal the lifetime mismatches among the power switching devices operating under the same condition, which offers new thoughts for a robust design and a reliable operation of grid-connected transformerless PV inverters with high efficiency.